Treatment Outcomes Of Tuberculosis Patients: Cohort 2014 In A Private Sector In Cali, Colombia - Fernandez, Liliana (American Lung Association, 2016)
According to the WHO´s global statistics there is an estimated 9 millon individuals with a developed Tuberculosis (TB) infection; 1.5 millon who have died from TB and 360.000 who tested HIV-positive. More specifically, in Colombia, there are around 12.000 cases reported annually; in other words, 24 cases out of 100.000 indivuals; most cases, nationally, originating from Valle del Cauca. Ojective: Describe de experience in the managing active tuberculosis patients in a referenced hospital in Cali, Colombia during 2014.